Wanita Minahasa - Geraldine Manoppo-Watupongoh (Antropologi Indonesia, 1995)
This article tries to explain the sttaus and role of women in Minahasa society. The author describes the image of Minahasa women in legends and folklore. It also describes the position of women in local culture such as in marriage and death, and in the division of labor. Based on historical data, the author gives several examples of events that reflect the character of Minahasa women. This article alsi describes contemporary activities of women in education, religion, and social organizations such as PIKAT, PERKIM, and Dharma Wanita.